2019
DOI: 10.3855/jidc.10556
|View full text |Cite
|
Sign up to set email alerts
|

β-lactamase genes in carbapenem resistance Acinetobacter baumannii isolates from a Turkish university hospital

Abstract: Introduction: The spread of Acinetobacter baumannii, resistant to most of the available antimicrobial agents, is a serious health problem. The high rate of carbapenem resistance among Acinetobacter baumannii isolates is considered as a threat to public health. In this study, we aimed to determine the antibiotic resistance and related genes in carbapenem-resistant Acinetobacter baumannii isolates. Methodology: Ninety six isolates of A. baumannii were included. Antimicrobial susceptibility was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…In this study, the resistance of the ABC strains to amikacin, ciprofloxacin, gentamisin, imipenem and meropenem were 78.8%, 85%, 81.9%, 85.1% and 86.6%, retrospectively. In our study, the rates of resistance to the indicated antibiotics were consistent with the literature [23][24][25].…”
Section: Resultssupporting
confidence: 91%
“…In this study, the resistance of the ABC strains to amikacin, ciprofloxacin, gentamisin, imipenem and meropenem were 78.8%, 85%, 81.9%, 85.1% and 86.6%, retrospectively. In our study, the rates of resistance to the indicated antibiotics were consistent with the literature [23][24][25].…”
Section: Resultssupporting
confidence: 91%
“…In a multicentre study conducted in 2016 in Turkey, 443 isolates of A. baumannii were studied, and CTX-M-1 was identified in 63 isolates and CTX-M-2 in 42 isolates [18]. The presence of CTX-M-1 and CTX-M-2 β-lactamases in 96 A. baumannii isolates from Turkey was investigated and no positive results were obtained for the isolates [19]. In the same study, the presence of OXA- [20].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that all the isolated strains were susceptible to tigecycline and colistin. However, there have been many reports of tigecycline and colistin resistance, which range from 0.6% to 45.8% [18][19][20][21] and 0 to 30.6%, respectively, around the world [22][23][24][25]. Furthermore, colistin resistance was reported to be of 4% in the EARS-Net 2016 report [26].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the discovery of bla OXA-23, the OXA enzymes were thought to be a small group of enzymes encoded by plasmids that affected only penicillins; the migration of these genes via transposons caused them to become the dominant mechanism of antibiotic resistance [4]. The frequency of bla OXA-23 in A. baumannii strains has been reported to range from 32% to 100% in Turkey [21,31,32] and from 28% to 96% worldwide [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation